Analysis of Manganese deposits from the Atlantic and Indian oceans - Willard S Moore (PANGAEA, 1973)
Accumulation rates of 1-2 mm/million years are reported for manganese crusts on deep-sea rocks. These rates are the same as most reported accretion rates for manganese nodules suggesting a similar mechanism for this formation. Manganese crusts on large deep-sea rocks provide convincing evidence that net sediment accumulation in these areas has been zero for many millions of years.
Supplement to: Moore, WS (1973): Accumulation rates of manganese crusts on rocks exposed on the sea floor. In: Phase I Report - Inter-University Program of Research on Ferromanganese Deposits of the Ocean Floor. Seabed Assessment Program, IDOE, NSF, Washington D.C., USA, 93-96, https://store.pangaea.de/Projects/NOAA-MMS/Moore2_1973.pdf